My child's future mental health: Carer's engagement with risk identification in an intervention study for youth with at‐risk mental states. Issue 6 (19th August 2021) - Tham, Michael; Bendall, Sarah; Carlyon‐Stewart, Thomas; Polari, Andrea; Hartmann, Jessica; Kerr, Melissa; Amminger, Paul; McGorry, Patrick; Nelson, Barnaby; Ratheesh, Aswin
Abstract: Aim: Prevention and early intervention efforts of serious mental illnesses has yielded promising results. However, alongside benefits, several ethical concerns have been raised, including the effects of being identified as being at‐risk. In these debates, the voice of parents or carers is conspicuously absent. This is especially concerning as several at‐risk interventions are trialled in under‐age youth where parents consent on behalf of young people. Therefore, this study aimed to understand carer's experiences of their teenager being identified as at risk for psychosis. Methods: Semi‐structured interviews were conducted with seven carers who had provided consent for their teenager to participate in a stepped intervention study for youth at‐risk for psychosis. Questions explored their experiences regarding having their teenager being identified as at‐risk. Transcripts were analysed using thematic analysis. Results: We identified five main themes from seven female carers' experiences of risk identification including: (a) recall of risk information was limited, or variable, (b) goal of risk disclosure was perceived to be positive, (c) negative emotions were associated with knowledge of risk, (d) relief from uncertainty and helplessness and (e) effects of risk disclosure were mediated by individual circumstance. Conclusion: Overall, the results demonstrate that carers' experience of risk disclosure varied with factors surrounding their individual circumstances, and the process of disclosure. Whilst participants acknowledged potential adverse effects associated with risk disclosure, many still adopted a positive outlook. Tailoring safe and effective disclosure of risk to suit the needs of youth and carers could outweigh the potential risks.